Studying the Mechanobiology of Aortic Endothelial Cells Under Cyclic Stretch Using a Modular 3D Printed System - Aguilera Suarez, Sergio; Sekar, Nadia Chandra; Nguyen, Ngan; Lai, Austin; Thurgood, Peter; Zhou, Ying; Needham, Scott; Pirogova, Elena; Khoshmanesh, Khashayar; Baratchi, Sara (Frontiers in Bioengineering and Biotechnology, 2021)
Here, we describe a motorized cam-driven system for the cyclic stretch of aortic endothelial cells. Our modular design allows for generating customized spatiotemporal stretch profiles by varying the profile and size of 3D printed cam and follower elements. The system is controllable, compact, inexpensive, and amenable for parallelization and long-term experiments. Our proof-of-concept experiments using human aortic endothelial cells show significant changes in the cytoskeletal structure and morphology of cells following exposure to 5% and 10% cyclic stretch over 9 and 16 hours. The system enables exploring the complex molecular and cellular processes governing the response of mechanosensitive cells under cyclic stretch.